login
A132044
Triangle T(n,k) = binomial(n, k) - 1 with T(n,0) = T(n,n) = 1, read by rows.
15
1, 1, 1, 1, 1, 1, 1, 2, 2, 1, 1, 3, 5, 3, 1, 1, 4, 9, 9, 4, 1, 1, 5, 14, 19, 14, 5, 1, 1, 6, 20, 34, 34, 20, 6, 1, 1, 7, 27, 55, 69, 55, 27, 7, 1, 1, 8, 35, 83, 125, 125, 83, 35, 8, 1, 1, 9, 44, 119, 209, 251, 209, 119, 44, 9, 1
OFFSET
0,8
COMMENTS
Row sums = A132045: (1, 2, 3, 6, 13, 28, 59, ...).
The triangle sequences having the form T(n,k,q) = binomial(n, k) + q^n*binomial(n-2, k-1) - 1 have the row sums Sum_{k=0..n} T(n,k,q) = 2^(n-2)*q^n + 2^n - (n-1) - (5/4)*[n=0] -(q/2)*[n=1]. - G. C. Greubel, Feb 12 2021
FORMULA
T(n, k) = A007318(n,k) + A103451(n,k) - A000012(n,k), an infinite lower triangular matrix.
T(n, k) = binomial(n, k) - 1, with T(n,0) = T(n,n) = 1. - Roger L. Bagula, Feb 08 2010
From G. C. Greubel, Feb 12 2021: (Start)
T(n, k, q) = binomial(n, k) + q^n*binomial(n-2, k-1) - 1 with T(n, 0) = T(n, n) = 1 and q = 0.
Sum_{k=0..n} T(n, k, 0) = 2^n - (n-1) - [n=0]. (End)
EXAMPLE
First few rows of the triangle:
1;
1, 1;
1, 1, 1;
1, 2, 2, 1;
1, 3, 5, 3, 1;
1, 4, 9, 9, 4, 1;
1, 5, 14, 19, 14, 5, 1;
1, 6, 20, 34, 34, 20, 6, 1;
1, 7, 27, 55, 69, 55, 27, 7, 1;
MATHEMATICA
T[n_, k_]:= If[k==0 || k==n, 1, Binomial[n, k] - 1];
Table[T[n, k], {n, 0, 12}, {k, 0, n}]//Flatten (* Roger L. Bagula, Feb 08 2010 *)
PROG
(Sage)
def T(n, k, q): return 1 if (k==0 or k==n) else binomial(n, k) + q^n*binomial(n-2, k-1) -1
flatten([[T(n, k, 0) for k in (0..n)] for n in (0..12)]) # G. C. Greubel, Feb 12 2021
(Magma)
T:= func< n, k, q | k eq 0 or k eq n select 1 else Binomial(n, k) + q^n*Binomial(n-2, k-1) -1 >;
[T(n, k, 0): k in [0..n], n in [0..12]]; // G. C. Greubel, Feb 12 2021
CROSSREFS
Cf. this sequence (q=0), A173075 (q=1), A173046 (q=2), A173047 (q=3).
Sequence in context: A161671 A144444 A054106 * A034327 A034254 A157103
KEYWORD
nonn,tabl
AUTHOR
Gary W. Adamson, Aug 08 2007
STATUS
approved